1997
DOI: 10.1590/s0100-879x1997000200006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of first morning urine volume, fasting blood glucose and glycosylated hemoglobin on first morning urinary albumin concentration

Abstract: The aim of the present study was to evaluate the effect of first morning urinary volume (collected on three different non-consecutive days), fasting blood glucose (determined on the first and third days of urine collection), and glycosylated hemoglobin (determined on the first and third days of urine collection) on the albumin concentration in first morning urine samples collected on three different days. We found 3.6% asymptomatic bacteriuria in the urine samples; therefore, every urine sample must be tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Our results are highly supported by already published reports [55], [56]. Diabetic nephropathy is a clinical manifestation of developed microalbuminuria that may be due to impaired tubular reabsorption and/or leakage of albumin due to injured glomeruli [57] that may leads to alteration of selective barriers of glomeruli. Urinary albumin and creatinine have been considered as defensive biomarkers for diagnosis of diabetic nephropathy [58].…”
Section: Discussionsupporting
confidence: 92%
“…Our results are highly supported by already published reports [55], [56]. Diabetic nephropathy is a clinical manifestation of developed microalbuminuria that may be due to impaired tubular reabsorption and/or leakage of albumin due to injured glomeruli [57] that may leads to alteration of selective barriers of glomeruli. Urinary albumin and creatinine have been considered as defensive biomarkers for diagnosis of diabetic nephropathy [58].…”
Section: Discussionsupporting
confidence: 92%
“…Gomes et al. [29] observed that developed albuminuria may be due to impaired tubular reabsorption or leakage of albumin due to damaged glomerular membrane, which leads to alterations in size or changes in selective barriers of the glomeruli.…”
Section: Discussionmentioning
confidence: 99%
“…In diabetes there is a relationship between glucose homeostasis and renal damage (Rasch, 1979a,b), and the early identification of microalbuminuria is considered to be clinically relevant (Gomes et al, 1997). This fact is very important because many reports have demonstrated that therapeutical intervention can delay the development of end-stage renal disease (Mathiesen et al, 1994).…”
Section: Discussionmentioning
confidence: 99%